Dancing with Ideology: Grammatical Metaphor and Identity Presentation in Translation - Zhu, Chunshen; Zhang, Junfeng (Meta, 2015)
This paper begins with an account of a high-profile political speech event centring on a Chinese slangy expression ‘[we] bu zheteng’ when it was used by the then Chinese President Hu Jintao in a 2008 speech, of which the Chinese government preferred a zero-translation despite the existing translations and various choices already available in Chinese-English dictionaries. The paper then discusses from the perspective of grammatical metaphor how and why an innocent-looking pragmatic usage has given rise to a series of ideologically charged debates over its translation. To that end, the paper conducts a critical review of grammatical metaphor, a key Systemic Functional Linguistic concept in describing congruence-to-metaphor evolution of language. Our cross lingual observation of this translation-related speech event enables us to argue that different textual means of presentation/concealment of human participation in transitivity are key to accounting for the discursive function of grammatical metaphors and to discerning the “chain” between congruent and metaphorical expressions. In the light of concealment of human participation in the transitivity process, the paper also observes that it is the association between the vague self-referencing ‘we’ and the adverse actions/situations, that is, (causing) commotions, alluded to by the term zheteng that has made a semantically explicit translation ideologically less desirable. As such, this operation of zero translation appears to be an instance of discursive manoeuvre rather than a sign of semantic impasse. To substantiate its theoretical claim, the paper relates the case to some similar political speech events in the world’s political arena and demonstrates how, prompted by this functional awareness of grammatical metaphors, one may devise a translation with better informed sensitivity to identity presentation/concealment in discourse.